2019
DOI: 10.1016/j.sjbs.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of physiological and biochemical markers for salt (NaCl) stress in the seedlings of mungbean [Vigna radiata (L.) Wilczek] genotypes

Abstract: Salt stress, which is dominant among environmental stresses, poses challenges to global agriculture. We studied the role of exogenous application of sodium chloride (NaCl) in three arid and three semi-arid genotypes of mungbean [ Vigna radiata (L.) Wilczek] by examining some physiological and biochemical stress indicators. Ten-day old seedlings were subjected to salt stress (00–250 mM) by split application along with the half strength Hoagland’s medium. The salt stress caused a decline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…The lowest MDA accumulation under salt stress was also observed in the salt-tolerant CSSL line of rice compared with the salt-sensitive CSSL line (Nounjan and Theerakulpisut 2012). This result agrees with the results reported for other plant species, such as strawberry (Garriga et al 2015), melon (Sarabi et al 2017), rice (Wang et al 2018), and mungbean (Alharby et al 2019). Moreover, a highly significant negative correlation was observed between MDA content and LRWC as well as photosynthesis (Table 3), suggesting lipid peroxidation, caused by salt stress, as one of the main reasons for the decrease of the tissue-water content and photosynthetic rate in cotton genotypes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lowest MDA accumulation under salt stress was also observed in the salt-tolerant CSSL line of rice compared with the salt-sensitive CSSL line (Nounjan and Theerakulpisut 2012). This result agrees with the results reported for other plant species, such as strawberry (Garriga et al 2015), melon (Sarabi et al 2017), rice (Wang et al 2018), and mungbean (Alharby et al 2019). Moreover, a highly significant negative correlation was observed between MDA content and LRWC as well as photosynthesis (Table 3), suggesting lipid peroxidation, caused by salt stress, as one of the main reasons for the decrease of the tissue-water content and photosynthetic rate in cotton genotypes.…”
Section: Discussionsupporting
confidence: 90%
“…Several previous reports have suggested that salt tolerant plants showed less biomass reduction and better growth under salt stress compared with salt-sensitive plants (Ahmed et al 2013;Singh and Sarkar 2014;Chiconato et al 2019). The reason may be primarily attributed to the functional impairment of the osmotic potential, followed by ionic imbalance, predictably leading to a nutritional disproportion in plants (Meloni et al 2001;Alharby et al 2019). Another possible mechanism for the lower biomass accumulation may be the diversion and/or exchange of potential energy from plant growth to sodium ion exclusion.…”
Section: Discussionmentioning
confidence: 97%
“…4) [76]. However, plant growth is inhibited, the chlorophyll levels and photosynthetic e ciency decrease in the nonhalophyte such as mung bean and Chinese cabbage under NaCl treatment [77,78]. In the present study, NaCl treatment signi cantly (P < 0.05) promoted the photosynthetic oxygen evolution capacity in petals and the photosynthetic e ciency in leaves of S. salsa plants (Additional le 4: Figure S4 and Fig.…”
Section: Discussionmentioning
confidence: 50%
“…The decrease in plant growth under salt stress was mainly due to the imbalance of nutrients. In addition, salt stress could inhibit cell division and cell elongation, and also reduce the extracellular water potential and water bioavailability of the root area of the plant, causing the plants had a low absorption of water and nutrients, which led to damage to the metabolic activity in the system [24]. Other studies had also found that tomato and wheat growth and biomass also decline under salt stress [2,25].…”
Section: Discussionmentioning
confidence: 99%
“…Salt-induced alterations in chlorophyll content may be due to salt stress caused Mg precipitation to impair biosynthesis, or to change the bond between chlorophyll and thylakoid membrane protein, increased Chl-degrading enzyme chlorophyllase activity and accelerated chlorophyll degradation, this effect is attributed to increased Na + content of toxic cations [31][32][33]. Salt stress also caused reduction in chlorophyll contents in mungbean leaves, which might be caused by membrane swelling in chloroplasts and/orexcess Na + ions in the leaves [24]. In this research, as expected, in the saltstressed plants, Na accumulated excessively in leaves (Fig.…”
Section: Discussionmentioning
confidence: 99%